Evaluating Technical Guidance in the Functional Role of Learning Facilitators: A Multidimensional Approach to Enhancing Educational Outcomes - Ratna Dumasari; Anan Sutisna; Puji Hadiyanti; Muhammad Mawardi (Journal of Nonformal Education, 2024)
The dynamic and multifaceted roles of educators in community education, this study emphasizes the essentiality of establishing a continuous and comprehensive evaluation mechanism. This study evaluates the role of technical guidance in supporting the functional responsibilities of these positions, employing a multidimensional approach to improve educational outcomes. Through a comprehensive evaluation system that incorporates continuous feedback, this research investigates the impacts of technical guidance on teaching practices and learning quality. Utilizing a descriptive quantitative methodological framework, this inquiry engaged 107 participants and 22 instructors from a technical guidance initiative, with a focus on systematically analyzing the initiative's efficacy within the educational milieu. The evaluative methodology employed herein encompasses an assessment of the cognitive, affective, and psychomotor dimensions of learning, utilizing descriptive statistical techniques to elucidate trends, patterns, and interrelations within the dataset. The findings of this scholarly investigation reveal that the technical guidance initiative has registered notable success in several domains, particularly in enhancing competencies and updating facilitators' insights regarding regulations and educational technologies. Nonetheless, it concurrently identifies domains necessitating enhancement, such as participant engagement and evaluative methods. The implications emanating from these findings bear significant ramifications for educational policy formulation and pedagogical practice. Recommendations proffered include the enhancement of material delivery clarity and engagement, diversification of implementation methodologies, refinement of assessment protocols, and an emphasis on the educators' well-being. This research furnishes a foundational basis for forthcoming endeavors aimed at optimizing technical guidance strategies, thereby augmenting the overall educational outcomes.